Contributions of depth filter components to protein adsorption in bioprocessing. Issue 8 (1st May 2018) - Khanal, Ohnmar; Singh, Nripen; Traylor, Steven J.; Xu, Xuankuo; Ghose, Sanchayita; Li, Zheng J.; Lenhoff, Abraham M.
Abstract: Depth filtration is widely used in downstream bioprocessing to remove particulate contaminants via depth straining and is therefore applied to harvest clarification and other processing steps. However, depth filtration also removes proteins via adsorption, which can contribute variously to impurity clearance and to reduction in product yield. The adsorption may occur on the different components of the depth filter, that is, filter aid, binder, and cellulose filter. We measured adsorption of several model proteins and therapeutic proteins onto filter aids, cellulose, and commercial depth filters at pH 5–8 and ionic strengths <50 mM and correlated the adsorption data to bulk measured properties such as surface area, morphology, surface charge density, and composition. We also explored the role of each depth filter component in the adsorption of proteins with different net charges, using confocal microscopy. Our findings show that a complete depth filter's maximum adsorptive capacity for proteins can be estimated by its protein monolayer coverage values, which are of order mg/m 2, depending on the protein size. Furthermore, the extent of adsorption of different proteins appears to depend on the nature of the resin binder and its extent of coating over the depth filter surface, particularly in masking the cation‐exchanger‐like capacity of the siliceous filter aids. In addition to guiding improved depth filter selection, the findings can be leveraged in inspiring a more intentional selection of components and design of depth filter construction for particular impurity removal targets. Abstract : Structural properties of depth filters and their components—filter aid, binder, and cellulose—were characterized and related to adsorption of proteins on the components and the filters. Adsorption appears dominated by electrostatic effects, leading to adsorption of predominantly positively and negatively charged proteins on the filter aids and on the binder‐coated depth filters, respectively. The extent of adsorption appears limited by monolayer coverage on the exposed filter surfaces.